The Effectiveness Of Transformative Experience With Analogy (Tewa) Module In Genetics Among Student Teachers - Kalimuthu, Ravintheran (2019)
The main aim of the study is to identify the prevalence of transformative experiences in genetics in terms of three interrelated qualities: motivated use; expansion of perception; and experiential value. The study also aimed to examine the effectiveness of transformative experience in overcoming misconceptions in relation to the topic genetics among student teachers enrolled in a Primary Science Education Programme in institute of higher learning. A total of 120 student teachers majoring in science from four Teacher Education Institutes in Malaysia participated in this study. A quasi-experimental design was used where the Transformative Experience With Analogy (TEWA) module adapted from Glynn (2007) was used as the intervention tool. Both quantitative and qualitative research instruments employed in this study. The quantitative instruments were the Transformative Experience Questionnaire (TEQ), Genetics Concept Diagnostic Test (GCDT). The qualitative instruments were the semi-structured interview questions on identifying student teachers misconceptions in genetics. Various descriptive and statistical analyses employed on the data collected. The results showed that the group, which underwent TEWA intervention, showed higher level of transformative experience and greater conceptual change than the comparison group. Implications for transformative experience as a conceptual change pedagogical technique discussed.